Lourenço Filho, Brasíl: 1897-1970 - de Souza Chaloba, Rosa Fatima [UNESP] (Taylor & Francis, 2025)
This chapter analyses the contribution of Lourenço Filho to the study of Comparative Education by discussing the conditions in which his book on the theme was produced and disseminated. This chapter argues that the success of the book Educação Comparada [Comparative Education] was partly due to Lourenço Filho’s prestige and acceptance in the field and the fact that its contents followed the prevailing approaches in the field based on the ideas of Isaac Kandel, Nicholas Hans, Joseph Lauwerys and Robert Ulich. These authors postulated the centrality of national education systems as an object of Comparative Education, with attention given to both the description and the dynamic understanding of the relations between education and society, thus prioritising the analysis of the socio-historical context. The chapter is divided into three parts: initially, it reconstructs the intellectual and professional trajectory of Lourenço Filho. Then, it examines his book on Comparative Education and, finally, synthetises the legacy of this educator to the field of Comparative Education.